Qur'anic Values That Shape Character and Heart: A Review of Surah Luqman Verse 18 - Mukhtarom, Asrori (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2025)
The purpose of this study is to determine the moral education contained in the Qur'an, letter Luqman verse 18. This study uses qualitative research with a literature review study or library research. The author uses primary/main sources, namely the Qur'an, supported by secondary sources such as books and articles in journals related to the theme of this study. The results of the study indicate that moral education is a process of forming good morals. The Qur'an is the main source of moral education. Moral education contained in the Qur'an, letter Luqman verse 18 is the prohibition of arrogant behavior. The reason arrogance is prohibited is because it causes Allah's wrath, causes not to enter heaven, causes conflict and war, and causes disharmonious relationships in the community. In the letter Luqman verse 18, it is explained that the role of parents in forming good morals in children is very important. Luqman is a parent who provides an example for his children. The results of this study are very useful for the world of education, especially the education process at home as the main and first educational institution for children. Keywords: Education, Moral, Al-Qur’an